2004
DOI: 10.1016/j.ijcard.2003.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme and p22phox polymorphisms and the risk of coronary heart disease in a low-risk Spanish population

Abstract: OBJECTIVE:To evaluate the genetic contribution to myocardial infarction in a homogeneous Caucasian population (a Mediterranean Spanish population) with very low frequency of coronary heart disease (CHD). DESIGN:We analyzed a total of 210 subjects, younger than 55 years, considered to be a low-risk population (104 cases of myocardial infarction and 106 control), and genotyped them (using polymerase chain reaction and sequencing) for the angiotensin-converting enzyme (ACE) insertion/deletion (ACE I/D) and for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
2
21
0
2
Order By: Relevance
“…The frequency of the T allele described for healthy subjects is less common in Japanese (0.07-0.13) and Chinese (0.066) than in European and Australian Caucasians (0.23-0.31). [17][18][19][20][21][22] The frequency of the T allele in Venezuelans reported in this study was comparable to that previously described for Caucasians, as the T allele was found in 27% of the Venezuelan subjects studied (present study). These findings are consistent with previous observations, where the frequency of both the alpha adducin and the eNOS polymorphisms described for Venezuelans was comparable to that of Anglo-Saxons and Spanish Caucasians, and significantly different from that of Orientals and African-Americans.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The frequency of the T allele described for healthy subjects is less common in Japanese (0.07-0.13) and Chinese (0.066) than in European and Australian Caucasians (0.23-0.31). [17][18][19][20][21][22] The frequency of the T allele in Venezuelans reported in this study was comparable to that previously described for Caucasians, as the T allele was found in 27% of the Venezuelan subjects studied (present study). These findings are consistent with previous observations, where the frequency of both the alpha adducin and the eNOS polymorphisms described for Venezuelans was comparable to that of Anglo-Saxons and Spanish Caucasians, and significantly different from that of Orientals and African-Americans.…”
Section: Discussionsupporting
confidence: 87%
“…However, clinical studies searching for the association of the polymorphism with cardiovascular diseases have provided contradictory results. Although the T allele appeared to confer cardiovascular risk protection in some studies, 16,17,20,[25][26][27] either no protection or increase risk was found in others. 15,17,21,22 In fact, the C242T polymorphism was found associated with coronary artery spasm, 15 coronary artery disease, 21 cerebrovascular disease and with atherothrombotic infarction.…”
Section: Nad(p)h Polymorphisms Cardiovascular Risk Factors and Cardimentioning
confidence: 94%
“…3) Equal risk in His72Tyr carriers was described for cardiovascular disease or risk factors (123,287,484,533,586,812,827). One study also reports equal risk for cardiovascular risk factors, but increased salt sensitivity and decreased levels of nitric oxide metabolites in His72Tyr carriers (129).…”
Section: Subunits and Regulatory Proteinsmentioning
confidence: 99%
“…One study (Katakami et al, 2009) was excluded since it was overlapped by another study with a larger scale (Katakami et al, 2010). Three publications did not meet the requirements of HWE (P HWE <0.05) (Mata-Balaguer et al, 2004;Morgan et al, 2007;Hashad et al, 2014). Finally, a total of 10 casecontrol studies were retrieved on ACS and the CYBA C242T polymorphism (Gardemann et al, 1999;Stanger et al, 2001;Yamada et al, 2002;Murase et al, 2004;Vasiliadou et al, 2006;Macías-Reyes et al, 2008;Katakami et al, 2010;de Caterina et al, 2011;Goliasch et al, 2011;Narne et al, 2012).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%